Understanding cancer genetic risk assessment motivations in a remote tailored risk communication and navigation intervention randomized controlled trial. Issue 1 (31st December 2022) - Le Compte, Circe Gray; Lu, Shou-En; Ani, Julianne; McDougall, Jean; Walters, Scott T.; Toppmeyer, Deborah; Boyce, Tawny W.; Stroup, Antoinette; Paddock, Lisa; Grumet, Sherry; Lin, Yong; Heidt, Emily; et al.
ABSTRACT: Background: National guidelines recommend cancer genetic risk assessment (CGRA) (i.e. genetic counseling prior to genetic testing) for women at increased risk for hereditary breast and ovarian cancer (HBOC). Less than one-half of eligible women obtain CGRA, leaving thousands of women and their family members without access to potentially life-saving cancer prevention interventions. Purpose: The Genetic Risk Assessment for Cancer Education and Empowerment Project (GRACE) addressed this translational gap, testing the efficacy of a tailored counseling and navigation (TCN) intervention vs. a targeted print brochure vs. usual care on CGRA intentions. Selected behavioral variables were theorized to mediate CGRA intentions. Methods: Breast and ovarian cancer survivors meeting criteria for guideline-based CGRA were recruited from three state cancer registries ( N = 654), completed a baseline survey, and were randomized. TCN and targeted print arms received the brochure; TCN also participated in a tailored, telephone-based decision coaching and navigation session grounded in the Extended Parallel Process Model and Ottawa Decision Support Framework. Participants completed a one-month assessment. Logistic regression was used to compare the rate of CGRA intentions. CGRA intentions and theorized mediator scores (continuous level variables) were calculated using mixed model analysis. Results: CGRA intentions increased for TCN (53.2%) vs. targeted print (26.7%) (OR = 3 .129; 95% CI: 2.028, 4.827, p < .0001) and TCN vs. usual care (23.1%) (OR = 3 .778, CI: 2.422, 5.894, p < .0001). Perceived risk ( p = 0.023) and self-efficacy ( p = 0.035) mediated CGRA intentions in TCN. Conclusions: Improvements in CGRA intentions and theorized mediators support the use of a tailored communication intervention among women at increased HBOC risk. (Clinicaltrials.gov: NCT03326713.) Trial registration: ClinicalTrials.gov identifier: NCT03326713 .